Personnel Management in Government : Politics and Process - Riccucci, Norma, Naff, Katherine (CRC Press, 2008)
Human resources represents one of the largest shares of government budgets at every level. The management of people who carry out the government's work is therefore a critical issue to politicians and government managers and leaders, as well as citizens. Regardless of which administration is in office or which reforms are being touted as necessary, personnel are always at the heart of government and governing.